Applications of Natural Violet Pigments from Halophilic Chromobacterium violaceum PDF23 for Textile Dyeing with Antimicrobial and Antioxidant Potentials. (23rd July 2022) - Anahas, Antonyraj Matharasi Perianaika; Kumaran, Subramanian; Kandeel, Mahmoud; Muralitharan, Gangatharan; Silviya, Jenifer; Adhimoolam, Geja Lakshmi; Panagal, Mani; Pugazhvendan, Sampath Renuka; Suresh, Gopal; Wilson Aruni, A.; Rethinam, Senthil; Prasannabalaji, Nainangu
Abstract : Natural colorants have emanated as a significant substitute to highly toxic synthetic dyes. The present study highlights the dyeing efficiency of violet pigment produced from Chromobacterium violaceum PDF23. A halophilic bacterium C. violaceum PDF23 produce violet pigments were isolated from the Great Salt Lake situated in Chennai, India. Based on morphology and 16S rRNA gene sequencing, a halophilic bacterium was identified as C. violaceum PDF23. The violet dye from C. violaceum PDF23 exhibited antimicrobial efficacy against S. aureus, B. subtilis, E. coli, P. aeruginosa, and C. albicans . The violet pigment exhibited radical scavenging potential with IC50 value of 14.40 μ g/mL. The dye ability of colorant was evaluated using mordants on two distinct fabrics, i.e., silk satin and cotton, and colorfastness measurements were recorded. The CIE L ∗ a ∗ b ∗ qualities of the dyed fabrics were assessed, as well as their colorfastness quality. The current research findings suggest that violet pigment has potent antimicrobial and antioxidant activity and it could be used as alternative to synthetic dye in the textile industry.